2012
DOI: 10.1111/j.2042-7158.2012.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective efficacy of chrysin against cisplatin-induced toxicity via attenuation of oxidative stress

Abstract: Objectives  Cisplatin‐induced nephrotoxicity is the main cause for its dose‐limited use in the treatment of various cancers and results in acute renal cell injury through generation of reactive oxygen species. Chrysin possess antioxidant, anti‐inflammatory and anti‐cancer properties. The aim of this study was to investigate the protective efficacy of chrysin against cisplatin‐induced nephrotoxicity. Methods  Thirty male Wistar rats were divided into five groups with six rats in each group. Group I served as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…It was also reported to increase the enzymatic and nonenzymatic antioxidant status, thereby conferring protection against ototoxicity. Previous experimental studies demonstrated that chrysin shows protective efficacy against cisplatin-induced toxicity of various tissues, such as kidney, colon, and jejunum, by attenuating oxidative stress and apoptotic tissue damage [38][39][40]. Sultana et al [38] examined the nephroprotective efficacy of chrysin against cisplatin toxicity, administering cisplatin and various concentrations of chrysin to Wistar rats for 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported to increase the enzymatic and nonenzymatic antioxidant status, thereby conferring protection against ototoxicity. Previous experimental studies demonstrated that chrysin shows protective efficacy against cisplatin-induced toxicity of various tissues, such as kidney, colon, and jejunum, by attenuating oxidative stress and apoptotic tissue damage [38][39][40]. Sultana et al [38] examined the nephroprotective efficacy of chrysin against cisplatin toxicity, administering cisplatin and various concentrations of chrysin to Wistar rats for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies demonstrated that chrysin shows protective efficacy against cisplatin-induced toxicity of various tissues, such as kidney, colon, and jejunum, by attenuating oxidative stress and apoptotic tissue damage [38][39][40]. Sultana et al [38] examined the nephroprotective efficacy of chrysin against cisplatin toxicity, administering cisplatin and various concentrations of chrysin to Wistar rats for 14 days. They reported that pretreatment with chrysin attenuated cisplatin-induced renal oxidative damage by diminishing DNA damage and increasing the enzymatic (catalase, glutathione reductase, glutathione-S-transferase, and glutathione peroxidase) and nonenzymatic (reduced glutathione) antioxidant status [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the risk of renal failure (26). The measurements of creatinine, urea, and uric acid are considered a tool in the clinical diagnosis of renal dysfunction following acute and chronic oxidative kidney injury (27,28). The increased level of Ni in the kidney that was observed after Ni treatment could be explained by high affinity of metallothionein, a metal binding protein for Ni (29).…”
Section: Kidney Histopathological Changesmentioning
confidence: 99%
“…A bulk of studies have shown that chrysin possesses diverse pharmacological activities including antivirus (Wang et al, 2014), antioxidant (Sultana et al, 2012), anti-tumor (Yu et al, 2013b), anxiolytic (Zanoli et al, 2000), neuroprotection (Kandhare et al, 2014), and anti-diabetes (Ahad et al, 2014;Li et al, 2014). Various mechanisms are involved in chrysinmediated health benefits such as attenuation of inflammation (Rehman et al, 2013), alleviation of oxidative stress (Mantawy et al, 2014), and induction of cell cycle arrest and apoptosis (Rashid et al, 2014).…”
Section: Introductionmentioning
confidence: 99%